Obesity and Its Impact on Adverse In-Hospital Outcomes in Hospitalized Patients With COVID-19 - Keller, Karsten; Sagoschen, Ingo; Schmitt, Volker H.; Sivanathan, Visvakanth; Espinola-Klein, Christine; Lavie, Carl J.; Münzel, Thomas; Hobohm, Lukas (Frontiers in Endocrinology, 2022)
Background An increasing level of evidence suggests that obesity is not only a major risk factor for cardiovascular diseases (CVD), but also for adverse outcomes during COVID-19-infection. Methods We used the German nationwide inpatient sample to analyze all hospitalized patients with confirmed COVID-19 diagnosis in Germany January-December 2020 and strati-fied them for diagnosed obesity. Obesity was defined as body-mass-index ≥30 kg/m² according to the World Health Organization. Impact of obesity on in-hospital case-fatality and adverse in-hospital events comprising major adverse cardiovascular and cerebrovascular events (MACCE), acute respiratory distress syndrome (ARDS), ve-nous thromboembolism (VTE) and others was analyzed. Results We analyzed data of 176,137 hospitalizations of patients with confirmed COVID-19-infection; among these 9383 (5.3%) had an additional obesity diagnosis. Although COVID-19-patients without obesity were older (72.0 [IQR 56.0 / 82.0] vs. 66.0 [54.0 / 76.0] years, P<0.001), the CVD profile was less favourable in obese COVID-19-patients (Charlson comorbidity index 4.44 ± 3.01 vs. 4.08 ± 2.92, P<0.001). Obesity was independently associated with increased in-hospital case-fatality (OR 1.203 [95%CI 1.131-1.279], P<0.001) and MACCE (OR 1.168 [95%CI 1.101-1.239], P<0.001), ARDS (OR 2.605 [95%CI 2.449-2.772], P<0.001) and VTE (OR 1.780 [95%CI 1.605-1.973], P<0.001), but also associated with increased necessity of treatment on intensive care unit (OR 2.201 [95%CI 2.097-2.310], P<0.001), mechanical ventilation (OR 2.277 [95%CI 2.140-2.422], P<0.001) and extracorporeal membrane oxygenation (OR 3.485 [95%CI 3.023-4.017], P<0.001). Conclusions Obesity independently affected case-fatality, MACCE, ARDS development, VTE and other adverse in-hospital events in patients with COVID-19 infection. Obesity should be taken into account regarding COVID-19 prevention strategies, risk stratification as well as for adequate health-care planning. Maintaining a healthy weight is not only important to prevent cardio-metabolic diseases, but also for better individual outcome during COVID-19-infection.